Perbandingan Pengaruh Latihan Diamond Push-up dengan Latihan Chair Push-up Terhadap Peningkatan Kekuatan Otot Lengan - Prasetio, Galih; Rohendi, Andang; Kurniawan, Asep Ridwan (Universitas Galuh, 2023)
The arm muscle strength that is focused on for expanded changes comes from the impact of precious stone push-ups and seat push-ups. The location of the research is Cilacap Regency's Komputama Majenang Vocational School. Understudies who were utilized as exploration objects were 20 individuals. Free experimental design was used as the research method. The estimation instrument utilized is push-ups. The obtained outcomes: 1. The precious stone push-up practice fundamentally affects positive changes in the arm muscle strength of understudies at SMK Komputama Majenang, Cilacap Rule. 2. Students at SMK Komputama Majenang, Cilacap Regency, experience significant improvements in arm muscle strength as a result of performing the chair push-up exercise. 3. At SMK Komputama Majenang, Cilacap Regency, students' increases in chair push-ups and diamond push-ups are significantly different. Conclusion: There is a positive change in the impact of precious stone push-ups and seat push-ups on arm muscle strength.